Ultrarapid MC1R protein and associated plumage color evolution in the domestic chicken - Cheng Ma; Aenne-Dorothea Liebing; Gunnar Kleinau; Antje Kamprad; Louisa Calabrese; Michal Szczepek; Zheng Li; Mårten Larsson; Patrick Scheerer; Claudia Stäubert; Leif Andersson (Proceedings of the National Academy of Sciences, 2026)
The domestic chicken exhibits extraordinarily high plumage diversity in sharp contrast to the uniform plumage phenotype in its wild ancestor, the red junglefowl. The melanocortin-1 receptor ( MC1R ) locus is the most variable pigmentation locus in domestic chicken. Here we have analyzed whole-genome sequence data from 10,026 birds, including red junglefowls and 393 populations of domestic chicken. We document ultrarapid evolution of 18 MC1R alleles, due to the accumulation of 9 missense mutations combined with reshuffling of sequence variants within the single MC1R exon. The lack of linkage disequilibrium at the MC1R locus strongly suggests that this combinatorial allele diversity is generated by interallelic gene conversion, possibly promoted by its high guanine–cytosine content. Functional analyses of MC1R variants expressed in transfected cells, using second-messenger and bioluminescence resonance energy transfer assays together with homology modeling, demonstrate that most missense mutations have significant effects on MC1R signaling and include both activating and inhibitory changes. One common MC1R allele differs by as many as three functionally relevant missense mutations from the most closely related wild-type allele, and its phenotype reflects their combined effects. Genome-wide analyses further show that MC1R acts as a modifier of dominant white and recessive white phenotypes caused by mutations in premelanosome protein and tyrosinase , respectively. In both cases, MC1R alleles promote a pure white phenotype, either by enhancing eumelanin pigmentation (dominant white) or inhibiting eumelanin pigmentation (recessive white).